Maden işletmelerinde özel tükenmeye tabi varlıkların vergi mevzuatı ve tms/ tfrs açısından envanter ve değerlemesi - Hayırlıoğlu, Özge (My University, 2019)
Rekabetin yoğun olarak yaşandığı küresel dünyada sağlam temellere dayananekonomi, ülkelerin kalkınması açısından önemlidir. Ekonomik anlamda kalkınmanınsağlanmasında lokomotif sektörlerden birisi de madencilik sektörüdür. Bu sektörde,insan yaşamında ihtiyaç duyulan enerji elde edilmektedir. Çalışmamızın amacı,madencilik alanında faaliyet gösteren işletmelerin Vergi Mevzuatı ve TMS/ TFRSaçısından envanter ve değerleme farklılıklarını ortaya koymaktır.Çalışmamızda madencilik hakkında genel bilgilere yer verilmesinin yanı sıra,konu ile ilgili olarak yasal düzenlemeler, bu alanda yapılan muhasebe işlemleri ve sonaşamada konunun esasını oluşturan Özel Tükenmeye Tabi Varlıklardaki envanter vedeğerleme konularına değinilmiştir. Sonuç olarak, bir maden işletmesi üzerinde yapılanuygulama ile de Vergi Mevzuatı ve TMS/ TFRS açısından envanter ve değerlemearasında farklılıklara ulaşılmış olup değerlendirmelere yer verilmiştir.

The economy based on solid foundations is an important aspect for thedevelopment of countries in the global world where competition is intense. One of thelocomotive sectors in the economic development is the mining sector. This sectorproduce the energy needed in human life. The aim of our study is to reveal the inventoryand valuation differences of the enterprises operating in the field of mining in terms ofTax Legislation and Turkish Accounting Standards (TAS)/ Turkish Financial ReportingStandards (TFRS).In this study, besides the general information about mining, we have alsodiscussed the legal regulations related to the subject, the accounting proceduresimplemented in this field and at the last stage, the inventory and valuation issues in thedepletable assets that represent our subject matter. As a result, it have been founddifferences between the application made in a mining enterprise and the inventory andvaluation made in terms of Tax Legislation and Turkish Accounting Standards(TAS)/ Turkish Financial Reporting Standards (TFRS) and the study included alsoevaluations in this regard.
Keywords: Değerleme; Depletable Assets; Envanter; Envanterler; Financial reporting standards; Finansal raporlama standartları; Inventories; Inventory; Maden araştırma; Maden İşletmeleri; Madencilik Faaliyetleri; Mining Activities; MiningOperations; Özel Tükenmeye Tabi Varlıklar; Prospecting; Tax Legislation; TMS/ TFRS; Turkey; Turkish AccountingStandards (TMS)/ Turkish Financial Reporting Standards(TFRS); Türkiye; Valuation; Vergi Mevzuatı